Active Patient Portal Status Negatively Correlated with Preterm Birth Rate Among Patients Seen in High Risk OB Clinic [32C]. (May 2018) - Cuff, Ryan D.; Wineland, Rebecca; Carter, Jessica; Sullivan, Scott; Johnson, Donna
Abstract : INTRODUCTION: Use of remote computer patient portals is increasing and thought to improve patient satisfaction, engagement in their care, and patient-provider communication. This study sought to evaluate the county-specific correlation between active patient portal status and preterm birth rate amongst patients under high risk obstetric care. METHODS: Descriptive population analysis of all obstetrical patients seen by maternal-fetal medicine at a single academic center from July 2016 through July 2017. Distinct patients were categorized according to their county of residence. Patient portal status, whether active or inactive, was then similarly determined by county. Counties were included if there were greater than 20 distinct patients seen within the established time frame. Preterm birth rates were obtained for each representative county from the Center for Disease Community Health Status Indicators database. Pearson's test was used to determine strength of correlation. RESULTS: 841 distinct patients representing seven counties met inclusion criteria. Active patient portal status ranged from 40.4% - 73.5%, while representative county-specific preterm birth rates ranged from 13.5% - 15.3%. Patient portal activity was negatively correlated with preterm birth rate, coefficient -0.77 (p. 0.04). CONCLUSION: There is a strongly negative correlation between active patient portal status and preterm birth rate amongst patients under high risk obstetrical care in South Carolina. Though descriptive, this finding suggests that the use of technology in medicine or patient connectivity may be an important correlate of disparate outcomes, and may exacerbate health disparities already known to exist for rural and disadvantaged populations.